SUSTAINABLE AGRICULTURE AND FUTURE CHALLENGES FOR AGRICULTURAL RESEARCH AND EXTENSION SERVICES - Milosević, Božidar; Lamberti, Lamberto (Economics of Agriculture, 2018)
Development policies in agriculture have been very effective in addressing the problems of agricultural productivity. However, this process caused a global growth in consumption of pesticides, inorganic fertilization components, animal feed-stuffs and heavy machinery. The transfer of technology, usually produced in developed countries, caused a depletion of natural resources and produced social and economic problems that, by neglecting the local knowledge and tradition together with applying not adaptive breeds and varieties, in fact, increased the problem of food insecurity worldwide. Nowadays, many evidences show that resource-conserving technologies and practices, incorporated into the framework of sustainable agriculture, can provide many benefits for farmers, even improved yields and productivity, with introducing only few, or no external inputs. There is a need for clear national strategy for agriculture and rural development with clearly defined points of sustainable agriculture. The role of research and extension services in implementation of such a strategy is irreplaceable. The present system of extension services has to be reformed in order to achieve the goals of sustainable agricultural development.